Analisis Penyebab Ketidaksesuaian Barang di Inventory dengan Aktual: Studi Kasus pada Perusahaan X Menggunakan Metode RCA - Muhammad Zidan Inprasepta; Aldi Allaudin; Nandana Malik Prayata; Anugrah Ramadhani Hidayah Warman; Yudi Prastyo (Journal of Engineering and Applied Technology, 2025)
This study examines stock accuracy performance, customer complaints, and the alignment between demand and fulfillment within a six-month operational period in order to identify the dominant factors contributing to inventory discrepancies. The findings show that variations in stock accuracy are closely related to nonstandard placement practices, non-real-time documentation, and inconsistencies in material movement across warehouse areas. Customer complaint records indicate recurring issues regarding wrong motif, wrong color, and shortage of delivered units, demonstrating that operational errors still play a substantive role. Additional analysis of demand and fulfillment across multiple ceramic sizes highlights that several product categories experience recurring gaps between requested and supplied quantities, particularly in the 60×60 WB variant. Root cause identification through a Pareto approach further reveals that human error, mixed materials in pallets, and misalignment between actual transfer and recorded data represent the largest contributors to overall discrepancies. These insights underscore the importance of strengthening warehouse discipline, enhancing personnel capability, and standardizing control mechanisms to ensure reliable inventory performance. The study concludes that structured interventions and continuous monitoring are required to maintain a stable and accurate stock management system.